Mechatronics electronic control systems in mechanical engineering - Bolton, W. (William) 1933- (Pearson Education Limited, 2015)
The integration of electronic engineering, mechanical engineering, control and computer engineering - Mechatronics - lies at the heart of the innumerable gadgets, processes and technology without which modern life would seem impossible. From auto-focus cameras to car engine management systems, and from state-of-the-art robots to the humble washing machine, Mechatronics has a hand in them all